2011
DOI: 10.1097/meg.0b013e32834b8d73
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and risk of gastric cancer

Abstract: These findings of this systematic review indicate that compared with nondiabetic individuals, diabetic women have an 18% increased risk of GC development. However, diabetic men have a similar risk of GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 56 publications
5
28
0
Order By: Relevance
“…However, male diabetes patients seem to be have a reduced risk of prostate cancer (RR= 0.85; 95% CI 0.80-0.91), which support the previous findings [9,10]. Furthermore, our findings support an increased risk of gastric and stomach cancer (RR=1.13; 95% CI 1.02-1.24), whereas former reports have been conflicting [15,16]. An elevation in thyroid cancer (RR=1.27; 95% CI 1.12-1.43) was also present among diabetes patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, male diabetes patients seem to be have a reduced risk of prostate cancer (RR= 0.85; 95% CI 0.80-0.91), which support the previous findings [9,10]. Furthermore, our findings support an increased risk of gastric and stomach cancer (RR=1.13; 95% CI 1.02-1.24), whereas former reports have been conflicting [15,16]. An elevation in thyroid cancer (RR=1.27; 95% CI 1.12-1.43) was also present among diabetes patients.…”
Section: Discussionsupporting
confidence: 89%
“…Several observational studies have examined the relationship between diabetes and gastrointestinal cancers. Results were conflicting in the meta-analyses on gastric cancer [15,16], while an increased risk of esophageal cancer was reported [13]. In addition, diabetes has been associated with an increased risk of colorectal cancer [17-19, 21-23] after adjustment for BMI and smoking [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among Asian population, except for Japanese population with a high incidence of this malignancy22, a modest increased risk of stomach cancer was observed in a study involving 895,434 T2DM patients in Taiwan15. Our analysis only showed a significant increased cancer risk in females, comparable to a recent meta-analysis of seventeen cohort studies and four case-control studies23 and a more recent meta-analysis of eleven cohort studies and six case-control studies24. Esophageal cancer showed a decreased risk in T2DM patients, which were consistent with findings from Asian population1525 and Australian females10.…”
Section: Discussionsupporting
confidence: 79%
“…More recently, DM has been shown to be associated with an increase in cancer risk by epidemiologic and mechanistic studies [3]. Observational studies have demonstrated increased risks of cancers of the pancreas [4], colon and rectum [5], esophagus [6], stomach [7], liver and bile ducts [8,9], urinary tract [10], breast [11], and the endometrium [1216] among patients with DM. Moreover, DM and increased serum glucose concentration have been associated with a rise in cancer-related mortality compared to the general population [17–19].…”
Section: Introductionmentioning
confidence: 99%